Implementasi Program Pagu Wilayah Kecamatan Bidang Ekonomi untuk Peningkatan Kapasitas Sosial dan Ekonomi Masyarakat di Kabupaten Temanggung - Yuni Astuti; Agnes Sunartiningsih (Journal of Social Development Studies, 2020)
The Government of the District of Temanggung implements the District Area Budget Ceiling Economic Program (economic PWK) to alleviate poverty towards acceleration of people's welfare improvement. Through the economic PWK, Temanggung Regency government provides a number of revolving working capital funds to poor communities at the district level as a means of capacity building and empowerment of communities both individually and in groups. Using descriptive qualitative research methods, this study aims to analyze the implementation of the program in Selopampang District in Temanggung Regency based on input, process, output, and outcome indicators. This research found that the implementation of economic PWK in Selopampang District, Temanggung District helped the poor in increasing economic and social capacity. Beneficiaries claim experiencing capacity improvement in terms of meeting their daily needs, accessing capital to build a business, and displaying their social roles in the community.